La place de l’imagination dans le dispositif didactique universitaire : une double fonction identitaire à créer - Marie-Pierre Dencuff (Éducation et Socialisation)
This contribution analyzes a university training device in French didactics at the primary level designed in the form of a digital portfolio and in which the imagination is called upon to play an important role. In an exploratory perspective, the work of future teachers integrated into a digital portfolio (N = 39) carried out in a Quebec university is analyzed. The theoretical foundations include the subject as socioculturally situated and for which the context of regulated activities and normative practices constitutes a didactic action (Brousseau, 1998) sedimented by the society (Giddens 1984/1987, Archer 1998), updated by the practices and institutionalized as a reference in time. The conclusions of the content analysis of the work (de Bonville, 2006) make it possible to formulate hypotheses on the relationships uniting the evolution of the subject with that of the teaching role. More specifically, concerning the dynamics established by this device and the relationship to knowledge for a) the linguistic and cultural dimension of the intellectual task and b) the professional dimension, starting a break with transmissive practices.